PKM Workshop Bagi Guru Di Kecamatan Somba Opu Kabupaten Gowa - Syamsurijal; Tjandi, Yunus; Tandirerung, Veronika Asri; Riana T. Mangesa; Prasojo, Kholik (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
This community service activity aims to help teachers in Somba Opu District, Gowa Regency as Partners in the Community Partnership Program (PKM). This assistance is in the form of: (1) improving student learning outcomes in several subjects which are still low, (2) developing teachers' knowledge about learning methods which are still limited. Teachers can choose various active, creative, effective and fun learning methods that suit the learning material, making it more interesting, more challenging and more fun. The methods used are: lecture, discovery learning, gallery walk, question and answer, with partners and carried out offline at Hasanuddin High School, Somba Opu District, Gowa Regency. The results achieved are (1) partners have developed their knowledge about various active, creative, effective and fun learning methods, (2) partners can carry out learning using various learning methods, (3) partners have the skills to design learning, (4) partners have the skills to carry out active, creative, effective and fun learning.